Effect of Substrate Temperature on Structural and Morphological Properties of Ga2O3 NPS Thin Films by (PLD) Method - Ali Sadam; Khalid Hameed Jebur; Wisam Ibrahim Taher (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In this study, thin films of Gallium oxide nanoparticles were deposited using the method ‎of ‎pulsed laser deposition (PLD) on a glass substrate under different ‏substrate temperatures ‏‎(400, 500,‎‏ ‏and ‎‎600 K ) before and after annealing. The Nd-YAG laser was utilized at the wavelength ( 1064 nm ) and the ‎frequency ‎‎(5 Hz) at 130 0C. The effect of substrate temperature value before and after annealing on the Structural and morphological Properties was studied by UV-VIS, X-ray diffraction ‎‏)‏XRD), scanning ‎electron ‎microscopy(SEM) and Atomic force microscopy (AFM) . The outcomes XRD showed ‎that the ‎structure of Ga2O3 nanoparticles is a polycrystalline structure of the monoclinic type with ‎Prominent crystal orientations of (-401), (-202), (- 111 ), (111), and (-312)‎‏.‏‎ It is ‎according to JCPDS card No.‎‏00‏‎-041-1103. Crystallite size for complete models increased with the growth substrate temperature value before and after annealing. The results of (SEM) for gallium oxide nanoparticles prepared ‎with ‎different substrate temperatures (400, 500, and 600 k) before and ‎after ‎annealing showed that the films increase their homogeneity and the ‎voids ‎decrease with increasing temperatures. The energy band gap decreased with increasing substrate temperatures, and the ‎absorption ‎ edge was in the UV zone..